Réponses

Meilleure réponse !
2014-09-28T22:59:20+02:00
G(x) = 2x+7-x²
on remplace x par les valeurs du tableau et on met le résultat dans le tableau sur la ligne g(x).
x = -2
g(-2) = 2*-2 +7 -(-2)² (* signifie multiplié par)
g(-2) = -4+7-4 = -1
x = -1
g(-1) = 2*-1+7-(-1)² = -2+7-1 = 4
x = 0
g(0) = 2*0+7-0² = 7
x = 0.5
g(0.5) = 2*0.5+7-(0.5)²  = 1+7-0.25 = 7.75
x = 1
g(1) = 2*1+7-1² = 2+7-1 = 8
x = 1.5
g(1.5) = 2*1.5+7-(1.5)²  =  3+7-2.25  = 7.75
x = 2
g(2) = 2*2+7-2² = 4+7-7 = 7
x = 3
g(3) = 2*3+7-3² = 6+7-9 = 4
x = 4
g(4) = 2*4+7-4² = 8+7-16 = -1